HOW MANY PLUMES ARE THERE? - Malamud B.D.; Turcotte D.L. (My University, 1999)
The objective of this paper is to quantitatively assess the role of mantle plumes in transporting heat to the base of the lithosphere. We first review the mechanisms responsible for mantle heat flow. We take the total global surface heat flow to be 4.43x1013 W. Of this, we attribute 0.68x1013 W (15%) to radiogenic heat production in the continental crust and 3.75x1013 W (85%) to heat loss from the mantle. Of the heat loss from the mantle, 2.17x1013 W (58%) is attributed to the subduction of the oceanic lithosphere and the remainder, 1.58x1013 W (42%), heats the base of the oceanic and continental lithosphere. Prior buoyancy studies of plumes give a plume heat flux of 0.24x1013 W, which is only 15% of the total heat flux associated with basal heating of the lithosphere. Thus, the amount that remains unaccounted for is a basal heat flux of 1.34x1013 W. The missing heat flux can be attributed either to plumes that do not have a significant surface expression, or to secondary mantle convection beneath the plates. We show that the cumulative frequency-size distribution of the large and intermediate size plume fluxes can be reasonably well approximated by a power-law distribution. We then extrapolate this distribution to smaller plumes in order to estimate a total plume heat flux. This requires about 5200 plumes, with the smallest plume fluxes about 109 W. This compares with 12x109 W for the smallest plume fluxes previously reported in the literature. We suggest that the large number of seamounts represents surface evidence for small plumes, and conclude that it is reasonable to attribute the entire basal heat flux to plumes.
Keywords: MANTLE PLUMES; HEAT FLOW; SEAMOUNTS; GEODYNAMICS; FRACTALS